Description of Level of Knowledge of Teenagers About Impact of Electric Cigarettes on Health in High School Students in Ambon City - Sahetapy, Beatries Giovany; Sitompul, Monalisa (Jurnal Biologi Tropis, 2025)
E-cigarettes, often known as vapes, have gained popularity as a substitute for traditional cigarettes in tandem with technological advancements. Since both contain nicotine, the harmful health effects are not appreciably different from those of traditional cigarettes. As of right now, there is not any solid scientific proof that e-cigarettes are a viable substitute for traditional cigarettes. This study aims to determine the level of knowledge of adolescents about the dangers of e-cigarettes to health. This study used a quantitative descriptive design. Data analysis used univariate analysis. The results found that the majority of respondents were female, namely 184 people (51.1%), while respondents of both genders. Knowledge of the dangers of e-cigarettes to health among adolescents was highest at 44 people (12.2%), with a moderate level of knowledge at 270 people (75%), and a low level of knowledge at 46 people (12.8%). Adolescent health education about the risks of e-cigarettes has to be improved, as seen by the comparatively low percentage of respondents (12.2%) who had high knowledge. The study concludes that education and health counseling are still necessary to increase adolescents' awareness of the risks associated with e-cigarettes, particularly since social media and the environment can give the false impression that e-cigarettes are safer than traditional cigarettes. These results highlight how crucial it is for families, schools, and medical professionals to provide correct and continuous education to raise teenagers' knowledge and awareness of the risks associated with e-cigarettes and so prevent their use at an early age.